An Optimal Management Model for Empty Freight Railcars in Transport Nodes - Rakhmangulov, Aleksadr; Osintsev, Nikita; Muravev, Dmitri; Legusov, Alexander (Operational Research in Engineering Sciences: Theory and Applications, 2019)
The paper presents the actual problem of increasing the efficiency of empty railcars management in rail nodes. This problem lies in considering the set of constraints. The main constraint is the requirement of railcars ‘owners on their loading by certain freights and sending to certain customers. This problem is complicated with the complexity of the traffic volumes structure that making them uneven. Hence, it creates an uneven loading factor of railway stations in the node. Moreover, railway stations are required to comply with the schedule of loading and unloading of railcars, as well as the schedule of trains and features of their formation in the rail nodes at large industrial enterprises. In order to optimally manage empty railcars at rail nodes, both the mathematical model and its solving method are presented. One of the distinctive features of the developed model lies in the application of a fuzzy logic method to evaluate online the loading factor of railway stations in the rail node. Moreover, this model takes into account these evaluations by optimizing the distribution of empty railcars at the loading points. The present study puts forward the method and algorithm of the developed mathematical model for empty railcars management. They could additionally take into account the possibility to include empty railcars groups in the composition of trains moving on schedule within large railway nodes or in systems of railway transport at large industrial enterprises. The proposed model significantly reduces the complexity of operational planning of dispatchers for distributing the empty railcar traffic volumes. Furthermore, the developed model minimizes the total handling time of railcars in rail nodes and ensures the timely supply of empty railcars to the loading points.